Light-emitting diodes effect on Aspergillus species in filtered surface water: DNA damage, proteome response and potential reactivation. (15th October 2021) - Oliveira, Beatriz R.; Marques, Ana P.; Asif, Muhammad; B. Crespo, Maria T.; Pereira, Vanessa J.
Abstract: DNA damage and changes in proteome response can occur as a consequence of UV light exposure. The emerging light-emitting diodes (LEDs) can be acquired with different wavelengths. In this study, LEDs that emit at 255 nm and 265 nm were selected to test the DNA damage and proteome response after inactivation of A. fumigatus, A. niger and A. terreus spiked into filtered surface water. Additionally, photoreactivation and dark repair studies were performed to evaluate the potential ability of the spores to recover after UV exposure. Results showed that both LEDs were able to induce the formation of cyclobutane pyrimidine dimers in A. fumigatus and A. terreus whereas, for A. niger, the formation of cyclobutane pyrimidine dimers was only detected when the LEDs that induced inactivation (that emit at 265 nm) were used. Proteome response showed that UV radiation treatment triggered different types of stress response, mainly concerning the protection from oxidative stress by A. fumigatus and A. terreus . Photoreactivation was detected for all the species except A. niger and, no dark repair was observed. Graphical abstract: Image 1 Highlights: Effect of light-emitting diodes on three different Aspergillus species. Assessment of cyclobutene pyrimidine dimers by an enzyme-linked immunosorbent assay. Proteome analysis using functional enrichment, gene ontology and REVIGO tools. Flow cytometry showed effects on membrane permeability and enzymatic activity. Reactivation under light and dark conditions of the fungal spores. Abstract : First report of the effect of UV-LEDs radiation that emit at 255 nm and 265 nm, on the DNA, proteome and potential reactivation of A. fumigatus, A. niger and A. terreus .